2017
DOI: 10.3126/jie.v12i1.16901
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fluoride Ions by Adsorption onto Fe<sub>2</sub>O<sub>3</sub> /Areca Nut Activated Carbon Composite

Abstract: Abstract:The possibility of Fe 2 O 3 /Areca nut activated carbon composite as an adsorbent for removal of fluoride from water is presented. Activated carbon (AC) was prepared from Areca nut by chemical activation with phosphoric acid at 400°C under nitrogen atmosphere. The resultant AC was characterized by adsorption of methylene blue and iodine. As indicated by iodine and methylene blue adsorption, the AC was highly micro and meso porous in nature. The adsorbent was prepared by compositing the AC with ferric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The methylene blue number was higher than that of other precursors except for areca nut and wood. The results suggested that phosphoric acid develops numerous micropores on the surface of activated carbon which can efficiently adsorb small ions from the aqueous solutions [18] 357 173 Rice husk [36] 367 196 Amaro seed stone [32] 371 256.42 Sugarcane bagasse [37] 814.67 198 Areca nut [38] 888 369 Wood(Thevetia peruviana) [39] 798 532…”
Section: Iodine and Methylene Blue Adsorptionmentioning
confidence: 99%
“…The methylene blue number was higher than that of other precursors except for areca nut and wood. The results suggested that phosphoric acid develops numerous micropores on the surface of activated carbon which can efficiently adsorb small ions from the aqueous solutions [18] 357 173 Rice husk [36] 367 196 Amaro seed stone [32] 371 256.42 Sugarcane bagasse [37] 814.67 198 Areca nut [38] 888 369 Wood(Thevetia peruviana) [39] 798 532…”
Section: Iodine and Methylene Blue Adsorptionmentioning
confidence: 99%
“…Up to the present only few adsorption studies have been carried out by making use of areca components. Activated carbon from areca nut, areca husk, areca coir and heart wood have been exclusively studied as adsorbent for the removal of dyes, acid and heavy metal ions (Joshi and adhikari, 2016;Muslim et al, 2017;Hemashree et al, 2016;Haloi et al, 2011;Chakrabarty et al, 2011). Congo red (CR) is a benzidine bisazo-dye which has variety of applications such as textile dying, indicator, biological stain etc.…”
Section: Introductionmentioning
confidence: 99%